2009
DOI: 10.1109/tbme.2008.2006029
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying Acute Myocardial Injury Using Ratiometric Fluorometry

Abstract: Early reperfusion is the best therapy for myocardial infarction (MI). Effectiveness, however, varies significantly between patients and has implications for long-term prognosis and treatment. A technique to assess the extent of myocardial salvage after reperfusion therapy would allow for high-risk patients to be identified in the early post-MI period. Mitochondrial dysfunction is associated with cell death following myocardial reperfusion and can be quantified by fluorometry. Therefore, we hypothesized that va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
28
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 23 publications
0
28
0
Order By: Relevance
“…Cellular NADH can be quantified by measuring the emitted fluorescence in tissue at approximately 450 nm after excitation with wavelengths of approximately 350 nm (Duchen, et al, 2003, White and Wittenberg, 1993). Many investigators have used this ratio to measure oxidative stress across multiple tissue types, including brain (Gerich, et al, 2009, Gerich, et al, 2006, Maleki, et al, 2012, Mayevsky, 1984, Parihar, et al, 2008, Ranji, et al, 2009) and this ratio has been established to be directly associated with tissue oxidative stress (Crowley, et al, 2015, Salehpour, et al, 2015). We and others found that this ratio can be measured in acutely-prepared brain slices, and is sensitive to small perturbations of molecules known to cause oxidative stress, such as hydrogen peroxide and cyanide (Gerich, et al, 2009, Gerich, et al, 2006, Stebbings, et al, 2016).…”
Section: 0 Backgroundmentioning
confidence: 99%
“…Cellular NADH can be quantified by measuring the emitted fluorescence in tissue at approximately 450 nm after excitation with wavelengths of approximately 350 nm (Duchen, et al, 2003, White and Wittenberg, 1993). Many investigators have used this ratio to measure oxidative stress across multiple tissue types, including brain (Gerich, et al, 2009, Gerich, et al, 2006, Maleki, et al, 2012, Mayevsky, 1984, Parihar, et al, 2008, Ranji, et al, 2009) and this ratio has been established to be directly associated with tissue oxidative stress (Crowley, et al, 2015, Salehpour, et al, 2015). We and others found that this ratio can be measured in acutely-prepared brain slices, and is sensitive to small perturbations of molecules known to cause oxidative stress, such as hydrogen peroxide and cyanide (Gerich, et al, 2009, Gerich, et al, 2006, Stebbings, et al, 2016).…”
Section: 0 Backgroundmentioning
confidence: 99%
“…Obtaining this information allows identification of the cases where the implantation of an Implantable Cardioverter-Defibrillator (ICD) device would be beneficial. Imaging techniques such as Contrast-Enhanced Cardiac Magnetic Resonance Imaging (CMR) can provide detailed information on the presence, location and extent of myocardial scar [4], [5]. However, in addition to its suitability only as a bedside test, CMR is a resource-demanding process, both in terms of cost and specialized personnel required for its operation.…”
mentioning
confidence: 99%
“…In cardiac surgery, indocyanine green (ICG), which is a type of fluorescent substance, is used to confirm blood perfusion after CABG surgery [11,12]. Furthermore, some studies have reported that autofluorescence exists in the myocardium and can be used to reflect mitochondrial viability in real time [13,14]. Fukuhiro et al [13] examined the fluorescence of nicotinamide adenine dinucleotide (NADH) with a CCD camera and an ultraviolet excitation light in a rat heart.…”
Section: Introductionmentioning
confidence: 99%
“…They concluded that it was possible to evaluate the change of myocardial NADH fluorescence during myocardial ischemia. Ranji et al [14] developed a catheter-like fluorescence measuring probe using a photomultiplier tube for NADH and flavoprotein (FP) in the myocardium. This in vivo study in rabbit hearts showed that the ratio of NADH to FP reflected the size of ischemia.…”
Section: Introductionmentioning
confidence: 99%